Mathematical modeling of wheelset oscillations as the basis of the method of acoustic control - Мартинов, Ігор Ернестович; Бондаренко, В’ячеслав Володимирович; Скуріхін, Дмитро Ігорович (Eastern-European Journal of Enterprise Technologies, 2014)
This publication argues the need for onboard condition monitoring of the railway car wheelsets in operation. Mathematical modeling of oscillations of the wheelset with short isolated irregularities on the surface of the rolling wheels was offered in the article. To solve the problem was developed three-dimensional finite element model of the wheelset type RU1SH-957. Mathematical modeling conducted in MSC Nastran. In determining the natural of frequencies and waveform of the railway car wheelset, the method Lanczos was applied as the most effective for most designs. We obtained results that maximum vibrodisplacement take place on the first natural frequency of oscillations of the wheelset wile motion with short isolated roughness on wheel surface. Definitely the speed of the car in which the forced vibrations of the action of periodic forces overlap, and the duration of the shock interaction between wheel and rail is not dependent on the speed of the car and the size of the roughness on the surface of the rolling wheel. The results are used for building acoustic diagnostic model and as boundary conditions in the simulation of field of wheelset noise emissions in undercar space